Whole exome sequencing in families at high risk for Hodgkin lymphoma: identification of a predisposing mutation in the KDR gene - Melissa Rotunno; Mary L. McMaster; Joseph Boland; Sara Bass; Xijun Zhang; Laurie Burdett; Belynda Hicks; Sarangan Ravichandran; Brian T. Luke; Meredith Yeager; Laura Fontaine; Paula L. Hyland; et al. (Haematologica, 2016)
Hodgkin lymphoma shows strong familial aggregation but no major susceptibility genes have been identified to date. The goal of this study was to identify high-penetrance variants using whole exome sequencing in 17 Hodgkin lymphoma prone families with three or more affected cases or obligate carriers (69 individuals), followed by targeted sequencing in an additional 48 smaller HL families (80 individuals). Alignment and variant calling were performed using standard methods. Dominantly segregating, rare, coding or potentially functional variants were further prioritized based on predicted deleteriousness, conservation, and potential importance in lymphoid malignancy pathways. We selected 23 genes for targeted sequencing. Only the p.A1065T variant in KDR (kinase insert domain receptor) also known as VEGFR2 (vascular endothelial growth factor receptor 2) was replicated in two independent Hodgkin lymphoma families. KDR is a type III receptor tyrosine kinase, the main mediator of vascular endothelial growth factor induced proliferation, survival, and migration. Its activity is associated with several diseases including lymphoma. Functional experiments have shown that p.A1065T, located in the activation loop, can promote constitutive autophosphorylation on tyrosine in the absence of vascular endothelial growth factor and that the kinase activity was abrogated after exposure to kinase inhibitors. A few other promising mutations were identified but appear to be “private”. In conclusion, in the largest sequenced cohort of Hodgkin lymphoma families to date, we identified a causal mutation in the KDR gene. While independent validation is needed, this mutation may increase downstream tumor cell proliferation activity and might be a candidate for targeted therapy.